Investment shocks and business cycles - Alejandro Justiniano; Giorgio E. Primiceri; Andrea Tambalotti (Federal Reserve Bank of Chicago, 2008)
Shocks to the marginal efficiency of investment are the most important drivers of business cycle fluctuations in US output and hours. Moreover, these disturbances drive prices higher in expansions, like a textbook demand shock. We reach these conclusions by estimating a DSGE model with several shocks and frictions. We also find that neutral technology shocks are not negligible, but their share in the variance of output is only around 25 percent, and even lower for hours. Labor supply shocks explain a large fraction of the variation of hours at very low frequencies, but not over the business cycle. Finally, we show that imperfect competition and, to a lesser extent, technological frictions are the key to the transmission of investment shocks in the model.
Keywords: 330; Investitionsklima; Arbeitsangebot; Schock; Unvollkommener Wettbewerb; Konjunktur; Dynamisches Gleichgewicht